2021
DOI: 10.48550/arxiv.2109.02713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Baryonic Imprints on DM Halos: Population Statistics from Dwarf Galaxies to Galaxy Clusters

Dhayaa Anbajagane,
August E. Evrard,
Arya Farahi

Abstract: In a purely cold dark matter universe, the initial matter power spectrum and its subsequent gravitational growth contain no special mass-or time-scales, and so neither do the emergent population statistics of internal dark matter (DM) halo properties. Using 1.5 million halos from three I TNG realizations of a ฮ›CDM universe, we show that galaxy formation physics drives non-monotonic features ("wiggles") into DM property statistics across six decades in halo mass, from dwarf galaxies to galaxy clusters. We chara… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…This expectation has since been confirmed for DMO and non-radiative simulations by Evrard et al (2008), whose meta-analysis found ๐›ผ = 0.3361 ยฑ 0.0026. Simulations with full baryonic physics treatments of galaxy formation find similar results for high mass halos (Lau et al 2010;Armitage et al 2018), but deviations of order 10% in amplitude are found as one moves toward lower mass halos (Anbajagane et al 2021).…”
Section: Dm Velocity Dispersion ๐œŽ Dmmentioning
confidence: 61%
See 3 more Smart Citations
“…This expectation has since been confirmed for DMO and non-radiative simulations by Evrard et al (2008), whose meta-analysis found ๐›ผ = 0.3361 ยฑ 0.0026. Simulations with full baryonic physics treatments of galaxy formation find similar results for high mass halos (Lau et al 2010;Armitage et al 2018), but deviations of order 10% in amplitude are found as one moves toward lower mass halos (Anbajagane et al 2021).…”
Section: Dm Velocity Dispersion ๐œŽ Dmmentioning
confidence: 61%
“…In principle, one could also add other halo properties to the scaling relation; studies of the I TNG simulations find that the scatter in ๐œŽ DM is strongly correlated with secondary DM halo properties such as concentration and shape (Anbajagane et al 2021) and so it is plausible, though not necessary, that these secondary properties correlate with ๐œŽ sat, 1D as well. At the halo mass scales of this study, Anbajagane et al (2021) show that the intrinsic variance in ๐œŽ DM can be reduced by a factor of 2 when concentration and velocity anisotropy are included in the regression.…”
Section: Ensemble Velocity Likelihood (Evl)mentioning
confidence: 99%
See 2 more Smart Citations
“…The location of shock features also depends closely on the mass accretion rate of the cluster and can potentially serve as an observational proxy for the same (Lau et al 2015;Shi 2016;Zhang et al 2020Zhang et al , 2021. The mass accretion rate has strong theoretical connections to key dark matter halo properties like concentration and formation time (Wechsler et al 2002), and has also been shown to have significant correlations with a broad range of halo properties (e.g., Lau et al 2021;Anbajagane et al 2021). However, it has remained difficult to infer observationally.…”
Section: Introductionmentioning
confidence: 99%